ANALYSIS OF THE RELATIONSHIP ANEMIA AND POSTPARTUM HEMORRHAGE IN ABDUL MOELOEK HOSPITAL, LAMPUNG CITY - Primasari, Sefria Indah (Journal of Applied Health Management and Technology, 2024)
The high prevalence of anemia affects almost all age groups in society. One of the groups of people with a high prevalence is pregnant women in various countries including Indonesia, reporting that the prevalence of anemia in the world is estimated at 30% of the world's population and around 500 million people are believed to suffer from anemia. Pregnancy anemia is called "potential danger to mother and child", which is why anemia requires serious attention from all parties involved in health services. Bleeding is the main factor causing high MMR. Bleeding can occur during pregnancy, childbirth and postpartum. Anemia is one of the risk factors that can worsen the mother's condition if accompanied by bleeding during pregnancy, childbirth and postpartum. Postpartum hemorrhage is still one of the causes of maternal death, which is 28%. Untreated postpartum hemorrhage can result in hemorrhagic shock, puerperal infection, and postpartum anemia. One of the predisposing factors of postpartum hemorrhage is anemia in pregnancy.This study aims to identify the relationship between anemia and postpartum hemorrhage in mothers. This study uses a quantitative approach with cross sectional and data analyzed univariately and bivariately. The subjects in this study were mothers giving birth at Abdul Moeloek Hospital, Lampung Province. The technique used in this study is a random sampling technique, namely subjects selected and taken randomly through a lottery. Data collection using secondary data and data analysis using Chi Square correlation.